Living in Diversity: Religious Moderation among Millennial Muslims in a Plural Indonesian Village - Noor Amirudin (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Indonesia's diverse society demands a tolerant attitude. However, it is a paradox in Indonesia's diverse society, the emergence of intolerant attitudes, radicalism and extremism, especially those targeting the millennial generation, is very worrying, for this reason it is necessary to build a moderate understanding. From this background, researchers are interested in examining the portrait of religious moderation based on al-Islam and Kemuhammadiyahan in the millennial generation in Balun Village Lamongan. Researchers used qualitative field methods with an interpretive phenomenological approach. The portrait of religious moderation based on al-Islam Kemuhammadiyahan in the millennial generation in Balun Village Lamongan is divided into four aspects, namely, (1) aqidah, where they interpret it as an essential belief that should not be mixed with other beliefs and beliefs or doubts about God inter-religious community; (2) ibadah (religious), where they tolerate each other in carrying out routine worship (religious rituals) so that there is interaction between the millennial generation across religions who uphold moderate values; (3) morals, where the millennial generation mutually enforce and uphold noble moral values ​​by being guided by the teachings of their respective religions; (4) muamalah (social community), where the millennial generation carries out activities in harmony and mutual cooperation without differentiating between their religions.